Grape Crushing and Traditional Wine Presses in Chile and Argentina (1550-1850) [Pisada de la Uva y Lagar Tradicional en Chile y Argentina (1550-1850)] - Rivas-Rodriguez, J; Lacoste, P; Soto-González, N (2011)
The wine press is a vessel where grapes are crushed and where the process of the elaboration of wine begins. It is relevant not only for its industrial and economic significance but also for its social and cultural implications. This article contributes to the understanding of the socioeconomic history of the region under study while at the same time serving as a contribution to the development of the recognition of the value of the traditional methods of the wine industry that once again are being used for the elaboration of Premium wines as well as for wine tourism.